THE UTILIZATION OF QRIS CODE FOR FINANCIAL MANAGEMENT OF THE AUTISM CAFE MALAYSIA - Taswanda Taryo; H. E. Nurzaman; Sarwani, Sarwani; Mukhlis Catio (Bajang Institute, 2024)
The Autism Café Project (PCA) Malaysia was founded in August 2016 by Adli Yahya, a father of an Autism Spectrum Disorder (ASD) child. With 7 ASD staff and 9 others, PCA provides ASD youth with a better future and a safe space to work. PCA allows them to reintegrate into society by having a cafe and 3 food stalls where they can train and work. One of the PCA issues is financial management for daily operations. The Collboration among PCA, Sultan Salahudin Syah Alam Polytechnic, Selangor, Malaysia and Pamulang University, Indonesia were held on 7 of March 2024 in Kualumpur. UNPAM Chancellor, Dr. E. Nurzaman, M.Si, M.M., Acting Director of Polytechnic Ts. Dr. Ahmad Aftas Bin Azman and PCA Manager provided knowledge sharing according to their expertise. A cooking demonstration by the ASD PCA was also given. PCA provided the results of the International Community Service (PKM-I) survey for the UNPAM Magister Management Study Program QRIS application for financial management and they concluded that financial management of PCA Malaysia has been effective and efficient since the first week of March 2024